ERGONOMICS AND HUMAN IN FOCUS: A SYSTEMATIC REVIEW OF RECENT DEVELOPMENTS - Novianti, Irma (Center for Study and Journal Management FTI UMI, 2024)
This systematic review investigates the incorporation of human factors and ergonomics into work system design, focusing on their effects on productivity and job satisfaction. By examining selected Q1 articles from the last five years, the review demonstrates that ergonomic interventions greatly reduce musculoskeletal disorders and improve employee engagement. These benefits arise from reduced physical strain and increased employee autonomy. Although awareness of ergonomic principles is on the rise, there remains inconsistency in their application across organizations. The review also discusses the role of modern technology, such as wearable devices, in advancing ergonomic practices, while noting potential challenges in adaptation. The findings highlight the critical need for organizations to implement comprehensive ergonomic strategies to create healthier and more productive work environments. Ongoing research and practical application of these principles are essential for developing effective workplace solutions that prioritize employee well-being.